Ultrahigh-temperature-resistant electrolyte and high-nickel metal lithium solid-state battery
By using in-situ polymerization in high-nickel metal lithium batteries, the problems of poor circulation performance and insufficient thermal stability of the battery in ultra-high temperature environment are solved, and the effect of stable circulation of hundreds of turns at 100℃ is achieved.
Patent Information
- Application Number
- CN202411933605.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
Existing high-nickel metal lithium batteries have poor circulation performance and insufficient thermal stability in ultra-high temperature environments, which are prone to battery gas production and thermal runaway.
Ultra-high temperature resistant electrolyte prepared by in-situ polymerization is used, which consists of high-stability lithium salts, pyrrole ionic liquids or ether solvents, multi-branched comonomers and initiators to form non-flowing elastic aggregates, enhance mechanical strength and inhibit the growth of lithium dendrites.
The battery's circulation performance and thermal stability are significantly improved at high temperatures, good interface stability is maintained, the battery's safety performance and cycle stability are enhanced, and the battery can be stable for a hundred cycles at ultra-high temperature of 100℃.
Smart Images

Figure CN119786713A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal lithium batteries, and in particular to a high-nickel metal lithium solid-state battery resistant to ultra-high temperature electrolyte. Background Art
[0002] In recent years, due to rising global temperatures and seasonal high-temperature weather, more and more applications urgently need to develop high-density energy batteries that can withstand high temperatures. The high-temperature cycle stability of metal lithium batteries is closely related to the stability of the cathode-electrolyte interface (CEI). At present, the commonly used cathode material for high-energy metal lithium batteries is nickel cobalt manganese oxide lithium ternary cathode (referred to as NCM), which has been widely studied due to its advantages such as high working voltage and energy density. Although high nickelization can improve the energy density of the battery, the higher the nickel content, the worse the thermal stability and the worse the cycle performance. At the same time, due to its own thermal instability, traditional electrolytes can only work stably at 60°C. Therefore, as the working temperature increases, the irreversible side reactions between the electrode and the electrolyte intensify, and the NCM high-energy metal lithium battery has a worse cycle performance at ultra-high temperatures (≥100°C), resulting in battery gas production and even thermal runaway. Therefore, it is urgent to develop a high-safety electrolyte (quality) with thermal stability, ultra-high temperature resistance (≥100°C), and adaptation to high-nickel cathodes.
[0003] At present, there is little research on electrolytes that are resistant to ultra-high temperatures (100°C) and suitable for high-nickel positive electrodes. The Chinese patent with publication number CN118173881A provides a high-temperature resistant flame-retardant electrolyte and its preparation method and application. The battery is composed of LiNi 0.5 Mn 1.5 The high temperature resistant electrolyte prepared in this patent is made of lithium hexafluorophosphate, lithium difluorooxalate borate sulfolane (SL), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and fluoroethylene carbonate (FEC). The battery prepared with this electrolyte was cycled 100 times at 60°C, and the capacity retention rate was 88.5%.
[0004] The Chinese patent with publication number CN115425292A provides a high temperature resistant electrolyte, secondary battery and its application, the high temperature resistant electrolyte includes lithium hexafluorophosphate, ethylene carbonate, diethyl carbonate, 1,3,5 trifluorobenzene and film-forming stabilizer p-toluenesulfonylmethyl isocyanide. The prepared lithium-ternary nickel cobalt manganese (Li-NCM622) battery was cycled 100 times at 3-4.3V, 1C rate charge and discharge, 60℃ high temperature environment, and the retention rate was 92%.
[0005] It can be seen that most batteries reported in the prior art have an operating temperature of 60°C or below, and there are currently few reports of metal lithium batteries that have both ultra-high temperature discharge performance and high specific energy. Summary of the invention
[0006] The object of the present invention is to provide a high-nickel lithium metal solid-state battery with ultra-high temperature resistant electrolyte to solve the problems in the above-mentioned background technology.
[0007] The technical solution adopted by the present invention is: an ultra-high temperature resistant electrolyte, the electrolyte is obtained by in-situ polymerization using the following raw materials: a basic electrolyte, a multi-branched copolymer monomer and an initiator, the basic electrolyte contains a lithium salt and an ultra-high temperature resistant main solvent, the concentration of the lithium salt in the basic electrolyte is 0.1 to 3 mol / L, and the ultra-high temperature resistant main solvent includes an ether solvent and / or a pyrrole ionic liquid.
[0008] Furthermore, the ether solvent is any one of ethylene glycol dimethyl ether, ethylene glycol n-butyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dibutyl ether and 18-crown-6.
[0009] Furthermore, the pyrrole ionic liquid is any one of 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide and N-methyl-N-methoxyethylpyrrolidine bis(trifluoromethanesulfonyl)imide.
[0010] Furthermore, the basic electrolyte contains additives, and the additives account for 3% to 5% of the mass of the basic electrolyte.
[0011] Furthermore, the additive is any two or three of lithium difluorooxalatoborate, 1,3-propylene sultone, lithium difluorophosphate, ethyl propionate, fluoroethylene carbonate and vinylene carbonate.
[0012] Furthermore, the lithium salt is any one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) and lithium difluorooxalatoborate.
[0013] Furthermore, the mass ratio of the basic electrolyte to the multi-branched copolymer monomer is (94.0-96.0):(4.0-6.0).
[0014] Furthermore, the multi-branched comonomer is any two of polyethylene glycol dimethacrylate, polyethylene glycol methyl ether acrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate and trifluoroethyl methacrylate; and the initiator is azobisisobutyronitrile or 1-((cyano-1-methylethyl)azo)formamide.
[0015] The technical solution of the present invention also includes: a high-nickel lithium metal solid-state battery, which includes a high-nickel positive electrode and the ultra-high temperature resistant electrolyte as described above, a ceramic solid electrolyte layer is constructed on the high-nickel positive electrode, and the ceramic solid electrolyte layer is located between the high-nickel positive electrode and the ultra-high temperature resistant electrolyte.
[0016] Furthermore, the ceramic solid electrolyte layer is a nano-scale LATP ceramic electrolyte layer, and its thickness is 450nm-500nm.
[0017] The invention has the beneficial effects that: the ultra-high temperature resistant electrolyte is prepared by in-situ thermal polymerization of a lithium salt with high stability, a pyrrole ionic liquid or an ether solvent, a multi-branched comonomer and an initiator; the ether solvent and the pyrrole ionic liquid selected by the invention are both ultra-high temperature resistant, high in ionic conductivity, stable to metallic lithium, excellent in cycle performance and thermal stability at high temperatures, and can maintain good interface stability; the ultra-high temperature resistant electrolyte obtained by in-situ thermal polymerization is a non-fluid elastic coagulation body, which can ensure uniform distribution of the electrolyte inside the battery, and the cross-linked network structure of the elastic coagulation body can enhance the mechanical strength and inhibit the growth of lithium dendrites, further improving the safety performance and cycle stability of the battery at high temperatures.
[0018] The high nickel positive electrode of the high nickel metal lithium solid-state battery is provided with a ceramic solid electrolyte, and the ceramic solid electrolyte layer is located between the high nickel positive electrode and the ultra-high temperature resistant electrolyte; the ultra-high temperature resistant electrolyte has a strong ion-dipole interaction at high temperature, and the solvation structure is stable. At high temperature and high electrical state, it can not only stabilize the structure of the positive electrode itself, improve the electrochemical properties of the high nickel material, but also prevent the metal lithium negative electrode from being reduced at high temperature, and form a stable interface film with the metal lithium negative electrode to reduce the occurrence of side reactions; the ceramic solid electrolyte can improve the interface compatibility between the positive electrode and the ultra-high temperature resistant electrolyte, and realize the full and stable performance of the positive electrode capacity. Through interface modification regulation and optimization, the physical contact between the electrode and the electrolyte is improved, which is conducive to solving the problem of difficult assembly of large-capacity solid-state batteries, interface compatibility and lithium dendrite short circuit caused by traditional liquid electrolytes. The ceramic solid electrolyte and the ultra-high temperature resistant electrolyte work synergistically to improve the safety performance and cycle stability of the high nickel metal lithium solid-state battery at high temperature. The prepared high nickel metal lithium solid-state battery has a high energy density and can be stably cycled for hundreds of times at an ultra-high temperature of 100°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the Arrhenius curve of the ultrahigh temperature resistant electrolyte prepared in Examples 1-5 of the present invention at 25-120°C;
[0020] Figure 2 1 is the DSC curve of the ultrahigh temperature resistant electrolyte prepared in Examples 1 and 4 of the present invention and the electrolyte prepared in the comparative example;
[0021] Figure 3 It is the first cycle energy curve of the high nickel metal lithium solid-state battery prepared in Examples 1-5 of the present invention and the metal lithium solid-state battery prepared in the comparative example;
[0022] Figure 4 It is a graph of the cycle capacity retention rate of the high-nickel metal lithium solid-state battery prepared in Examples 1 and 2 of the present invention and the metal lithium solid-state battery prepared in the comparative example. DETAILED DESCRIPTION
[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0024] The first aspect of the present invention provides an ultra-high temperature resistant electrolyte. In order to fully explain the technical solution, the present invention also discloses an embodiment of the preparation method thereof. In the present embodiment, the ultra-high temperature resistant electrolyte is obtained by in-situ polymerization using the following raw materials, and the raw materials include: a basic electrolyte, a multi-branched comonomer and an initiator. The basic electrolyte contains a lithium salt and an ultra-high temperature resistant main solvent. The lithium salt is a lithium salt with high thermal stability, and its concentration in the basic electrolyte is 0.1-3 mol / L. The ultra-high temperature resistant main solvent includes an ether solvent and / or a pyrrole ionic liquid. Since the high nickel material has a strong oxidizing property at a high electrical state, the oxidizing property will be stronger when placed in a high temperature environment, and metallic lithium is the metal element with the smallest atomic weight and the strongest reducing property, and the reducing property is even stronger at high temperature, and it is very easy to react with the electrolyte. The ether solvent and pyrrole ionic liquid selected in this embodiment are both resistant to ultra-high temperatures, and are stable to metallic lithium, and have excellent cycle performance and thermal stability at high temperatures. They can stabilize the structure of the positive electrode and the deposition of metallic lithium on the surface of the negative electrode at high temperatures and high electrical states, reduce the occurrence of side reactions, and improve the overall electrochemical performance of the high nickel battery.
[0025] Ether solvents can improve the electrode / electrolyte interface performance. Pyrrole ionic liquids are stable to metallic lithium, have high ionic conductivity, and have a stable solvation structure. They can maintain good interface stability between the electrode and the electrolyte, and can improve the safety and cycle stability of high-nickel metal lithium batteries in high temperature environments. The ultra-high temperature resistant electrolyte obtained by in-situ polymerization of the above raw materials is a non-fluid elastic aggregate, which can ensure the uniform distribution of the electrolyte inside the battery, and the cross-linked network structure of the elastic aggregate can enhance the mechanical strength and inhibit the growth of lithium dendrites, further improving the safety performance and cycle stability of the battery at high temperatures.
[0026] The lithium salt in this embodiment can be selected from any one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) and lithium difluorooxalate borate. When the ultra-high temperature resistant main solvent is an ether solvent, the concentration of the lithium salt in the basic electrolyte is preferably 2-3 mol / L, and when the ultra-high temperature resistant main solvent is a pyrrole ionic liquid, the concentration of the lithium salt in the basic electrolyte is preferably 0.1-1 mol / L.
[0027] In this embodiment, the ether solvent can be selected from any one of ethylene glycol dimethyl ether, ethylene glycol n-butyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dibutyl ether and 18-crown ether-6. The pyrrole ionic liquid can be selected from any one of 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide and N-methyl-N-methoxyethylpyrrolidine bis(trifluoromethanesulfonyl)imide.
[0028] In addition, the basic electrolyte in this embodiment also contains additives to promote positive and negative electrode film formation, inhibit gas generation, etc. The amount of additives added is preferably: its mass accounts for 3% to 5% of the mass of the basic electrolyte. The additives can be selected from any two or three of lithium difluorooxalatoborate, 1,3-propylene sultone, lithium difluorophosphate, ethyl propionate, fluoroethylene carbonate and vinylene carbonate.
[0029] The mass ratio of the basic electrolyte to the multi-branched comonomer is preferably (94.0-96.0): (4.0-6.0). More specifically: when the ultra-high temperature resistant main solvent is an ether solvent, the mass ratio of the basic electrolyte to the multi-branched comonomer is preferably (95.0-96.0): (4.0-5.0), and the initiator accounts for 0.1% to 1% of the total mass of the multi-branched comonomer. When the ultra-high temperature resistant main solvent is a pyrrole ionic liquid, the mass ratio of the basic electrolyte to the multi-branched comonomer is preferably (94.0-95.0): (5.0-6.0), and the initiator accounts for 0.05% to 0.5% of the mass of the basic electrolyte.
[0030] The multi-branched comonomer in this embodiment can be selected from any one of polyethylene glycol dimethacrylate, polyethylene glycol methyl ether acrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate (n≥2), and trifluoroethyl methacrylate; the initiator can be selected from azobisisobutyronitrile or 1-((cyano-1-methylethyl)azo)formamide.
[0031] When preparing the above-mentioned ultra-high temperature resistant electrolyte, the lithium salt is first dissolved to prepare a basic electrolyte, and then the multi-branched comonomer and initiator are added to the basic electrolyte and stirred to obtain a prepolymer solution, and the prepolymer solution is placed in an environment of 80°C for 2 to 10 hours for in-situ polymerization. More specifically: when the ultra-high temperature resistant main solvent is an ether solvent, the lithium salt and the ether solvent are mixed in proportion, stirred at a speed of 400rpm until the lithium salt is dissolved, and then the additive is added to the above-mentioned mixed solution, stirred at a speed of 400rpm for 12h, and then the multi-branched comonomer and initiator are added, and mixed and stirred for 8h; when the ultra-high temperature resistant main solvent is a pyrrole ionic liquid, the lithium salt and the pyrrole ionic liquid are mixed in proportion, stirred at a speed of 600rpm until the lithium salt is dissolved, and then the additive is added to the above-mentioned mixed solution, stirred at a speed of 600rpm for 12h, and then the multi-branched comonomer and initiator are added, and mixed and stirred for 8h.
[0032] The second aspect of the present invention provides a high-nickel lithium metal solid-state battery. In order to fully explain the technical solution, the present invention also discloses an embodiment of its preparation method. The high-nickel lithium metal solid-state battery in this embodiment includes a high-nickel positive electrode, a metal lithium negative electrode, a double ceramic coating diaphragm, the ultra-high temperature resistant electrolyte in the first aspect of the present invention, and other conventional structural components. Among them, a ceramic solid electrolyte layer is arranged on the high-nickel positive electrode, and the ceramic solid electrolyte layer is located between the high-nickel positive electrode and the ultra-high temperature resistant electrolyte. The ultra-high temperature resistant electrolyte has a strong ion-dipole interaction at high temperature, stabilizes the structure of the positive electrode itself at high temperature and high electrical state, improves the electrochemical properties of the high-nickel material, and has a stable solvation structure, and has a stable interface film with the metal lithium negative electrode, which can reduce the occurrence of side reactions; the ceramic solid electrolyte can improve the interface compatibility between the positive electrode and the ultra-high temperature resistant electrolyte, and realize the full and stable performance of the positive electrode capacity. Through interface modification regulation and optimization, the physical contact between the electrode and the electrolyte is improved, which is helpful to solve the difficulties in assembling large-capacity solid-state batteries, interface compatibility and lithium dendrite short-circuit problems caused by traditional liquid electrolytes. The ceramic solid electrolyte and ultra-high temperature resistant electrolyte work synergistically to improve the safety performance and cycle stability of high-nickel metal lithium solid-state batteries at high temperatures.
[0033] The high nickel positive electrode in this embodiment is constructed by slurry coating method, and the positive electrode slurry includes active material, conductive agent, binder and diluent. The active material is nickel-cobalt-manganese ternary positive electrode material, such as LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.92 Co 0.04 Mn 0.04Any one of the ternary type 9 positive electrode materials such as O2 (i.e. the Ni content in the positive electrode material is 90% or more); the conductive agent is any one or any two of conductive carbon black, conductive graphite, carbon fiber, carbon nanotubes and graphene; the binder is polyvinylidene fluoride-hexafluoropropylene; the diluent is N-methylpyrrolidone.
[0034] The ceramic solid electrolyte layer in this embodiment is preferably a nanoscale LATP ceramic electrolyte layer with a thickness controlled at 450nm to 500nm, which can not only prevent the positive and negative electrodes from short-circuiting when the battery system is overheated, and inhibit the chemical crosstalk heat generation between the positive and negative electrode systems, but also avoid internal dendrite piercing through the "needle-wrapping" effect, reduce short-circuit points, and regulate the surface compatibility of the positive electrode with the ultra-high temperature resistant electrolyte.
[0035] The ceramic solid electrolyte layer is constructed by ultrasonic spraying in a low dew point environment. After spraying, it is vacuum dried and the temperature is controlled at 110°C.
[0036] When preparing the above-mentioned high-nickel lithium metal solid-state battery, after constructing a ceramic solid electrolyte layer on the surface of the high-nickel positive electrode, punch it into a size suitable for the metal lithium negative electrode, and stack it with the metal lithium negative electrode and the double ceramic coating diaphragm through a semi-automatic stacking machine to assemble a high-nickel lithium metal battery dry cell; prepare a prepolymer solution of an ultra-high temperature resistant electrolyte, inject the prepolymer solution of the ultra-high temperature resistant electrolyte into the high-nickel lithium metal battery dry cell, and then place it in a vacuum device to evacuate, perform vacuum infiltration, and then seal the battery to obtain a preliminary infiltration battery; polymerize the preliminary infiltration battery in situ at 80°C for 2 to 10 hours to obtain a high-nickel lithium metal solid-state battery. In this embodiment, the injection amount of the prepolymer solution of the ultra-high temperature resistant electrolyte is preferably 1.8 to 2.0 g / Ah.
[0037] The prepared high-nickel lithium metal solid-state battery can be tested for performance by the following method: place the high-nickel lithium metal solid-state battery in an aluminum alloy clamp wrapped with Teflon tape, add a certain preload force to the battery, and then place the preloaded battery in an ultra-high temperature oven for static and electrical performance testing. In this embodiment, the preload force of the aluminum alloy clamp is 1.2N·m to 1.5N·m, the oven temperature is 100°C, and the static time is 6h.
[0038] The present technical solution is further described below through examples and comparative examples.
[0039] Example 1: Preparation of high nickel metal lithium solid-state battery
[0040] (1) High nickel positive electrode: constructed by slurry coating method, the active material in the positive electrode slurry is LiNi 0.9 Co 0.05 Mn 0.05O2, the conductive agent is conductive carbon black (SuperP), the binder is 6wt.% polyvinylidene fluoride-hexafluoropropylene, the mass ratio of the three is 96:2.5:1.5, after taking, add appropriate amount of N-methylpyrrolidone to dilute, stir well, and evenly coat on both sides of 9μm thick aluminum foil. After drying and rolling, the surface density is 19.2mg / cm 2 The positive electrode sheet is cut and punched to obtain an area of 39.6cm 2 High nickel positive electrode.
[0041] (2) Ceramic solid electrolyte layer: The high-nickel positive electrode was placed on the vacuum chuck of the ultrasonic spraying equipment, and the nano-scale LATP ceramic electrolyte slurry was evenly sprayed on the high-nickel positive electrode at a rate of 0.6 mL / min. The spraying was repeated 5 times. After drying, a high-nickel sprayed positive electrode containing a ceramic solid electrolyte layer with a thickness of about 460 nm was obtained.
[0042] (3) Metal lithium negative electrode: A 60 μm thick lithium foil was selected and punched to obtain a 42.18 cm 2 of metallic lithium anode.
[0043] (4) Lamination: After lamination by a semi-automatic lamination machine, 21 positive and 22 negative metal lithium battery cells are obtained. After welding the tabs and aluminum shell packaging, a 6.6Ah high-nickel metal lithium battery dry cell is obtained.
[0044] (5) Preparation of prepolymer solution: 1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide after dehydration with molecular sieve is used as the ultra-high temperature resistant main solvent, lithium salt LiTFSI is added thereto and mixed, wherein the lithium salt concentration is 0.6 mol / L, 2 wt.% LiODFB and 2 wt.% FEC are added and mixed to obtain a basic electrolyte; polyethylene glycol dimethacrylate and trifluoroethyl methacrylate are added to the basic electrolyte in a molar ratio of 1:1 (the total mass accounts for 5% of the basic electrolyte), and then CMAB initiator (accounting for 0.1% of the mass of the basic electrolyte) is added, and after stirring for 8 hours, a prepolymer solution is obtained.
[0045] The prepolymer solution of Example 1 was assembled into a blocked battery, and the EIS test showed that the ionic conductivity at 25°C and 100°C was 1.11×10 -3 S / cm, 6.86×10 -3 S / cm, see attached Figure 1 .
[0046] (6) In-situ polymerization: In an inert atmosphere, the prepolymer solution was injected into the high-nickel lithium metal battery dry cell at a liquid injection volume of 1.9 g / Ah, and then placed in a vacuum oven for evacuation twice, each time maintaining the pressure for 15 minutes (vacuum degree -0.08 MPa) to remove residual air inside the electrode. The battery was then sealed to obtain a preliminary impregnation battery; the preliminary impregnation battery was impregnated at room temperature and then subjected to in-situ polymerization in an oven at 80°C for 6 hours to finally obtain a high-nickel lithium metal solid-state battery.
[0047] The high nickel metal lithium solid-state battery of Example 1 was tested by the aforementioned test method. The energy value at constant volume at 100°C was 26.77Wh, and the specific energy was 416.8Wh / kg. Figure 3 After 160 cycles at 100℃, the capacity retention rate is 89.3%, see Appendix Figure 4 .
[0048] Example 2: Preparation of high nickel metal lithium solid-state battery
[0049] The only difference compared with Example 1 is that the prepolymer solution in Example 2 is prepared using the following scheme:
[0050] 1-Methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide after dehydration by molecular sieve is used as the ultra-high temperature resistant main solvent, and lithium salt LiTFSI is added thereto and mixed, wherein the lithium salt concentration is 0.6 mol / L, 1 wt.% LiPO2F2, 1 wt.% LiODFB and 2 wt.% FEC are added and mixed to obtain a basic electrolyte; polyethylene glycol dimethacrylate and trifluoroethyl methacrylate are added to the basic electrolyte in a molar ratio of 1:1 (the total mass accounts for 5% of the basic electrolyte), and then a CMAB initiator is added (accounting for 0.1% of the mass of the basic electrolyte), and after stirring for 8 hours, a prepolymer solution is obtained.
[0051] The prepolymer solution of Example 2 was assembled into a blocked battery, and the EIS test showed that the ionic conductivity at 25°C and 100°C was 1.55×10 -3 S / cm, 7.17×10 -3 S / cm, see attached Figure 1 .
[0052] The high nickel metal lithium solid-state battery of Example 2 was tested by the aforementioned test method. The energy value at constant volume at 100°C was 27.03Wh, and the specific energy was 421.0Wh / kg. Figure 3 After 160 cycles at 100℃, the capacity retention rate is 93.18%, see Appendix Figure 4 .
[0053] Example 3: Preparation of high nickel metal lithium solid-state battery
[0054] The only difference compared with Example 1 is that the prepolymer solution in Example 3 is prepared using the following scheme:
[0055] 1-Methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide after dehydration by molecular sieve is used as the ultra-high temperature resistant main solvent, and lithium salt LiTFSI is added thereto and mixed, wherein the lithium salt concentration is 0.6 mol / L, 1wt.% LiPO2F2, 1wt.% LiODFB and 2wt.% VC are added and mixed to obtain a basic electrolyte; polyethylene glycol dimethacrylate and trifluoroethyl methacrylate are added to the basic electrolyte in a molar ratio of 1:1 (the total mass accounts for 5% of the basic electrolyte), and then a CMAB initiator is added (accounting for 0.1% of the mass of the basic electrolyte), and after stirring for 8 hours, a prepolymer solution is obtained.
[0056] The prepolymer solution of Example 3 was assembled into a blocked battery, and the EIS test showed that the ionic conductivity at 25°C and 100°C was 1.18×10 -3 S / cm, 7.18×10 -3 S / cm, see attached Figure 1 .
[0057] The high nickel metal lithium solid-state battery of Example 3 was tested by the aforementioned test method. The energy value at constant volume at 100°C was 26.9Wh, and the specific energy was 418.9Wh / kg. Figure 3 After 160 cycles at 100°C, the capacity retention rate is 90.1%.
[0058] Example 4: Preparation of high nickel metal lithium solid-state battery
[0059] The only difference compared with Example 1 is that:
[0060] The prepolymer solution in Example 4 is prepared by the following scheme: tetraethylene glycol dimethyl ether after dehydration by molecular sieve is used as the ultra-high temperature resistant main solvent, the lithium salt LiFSI is added thereto and mixed, 2wt.% LiODFB, 2wt.% FEC and 1wt.% PES are added and mixed to obtain a basic electrolyte with a lithium salt concentration of 3 mol / L; polyethylene glycol dimethacrylate and triethylene glycol dimethacrylate are added to the basic electrolyte in a molar ratio of 1:1 (the total mass accounts for 4.5% of the basic electrolyte), and then a CMAB initiator is added (accounting for 0.5% of the total mass of the multi-branched copolymer monomer), and after stirring for 8 hours, a prepolymer solution is obtained.
[0061] The prepolymer solution of Example 4 was assembled into a blocked battery, and the EIS test showed that the ionic conductivity at 25°C and 100°C was 1.92×10 -3 S / cm, 7.3×10 -3 S / cm, see attached Figure 1 .
[0062] In the in-situ polymerization of Example 4: under an inert atmosphere, the prepolymer liquid was injected into the high-nickel lithium metal battery dry cell at an injection volume of 1.8g / Ah, and then placed in a vacuum oven for evacuation twice, each time maintaining the pressure for 15 minutes (vacuum degree -0.08MPa) to remove residual air inside the electrode, and then the battery was sealed to obtain a preliminary infiltration battery; the preliminary infiltration battery was infiltrated at room temperature and then in-situ polymerized in an oven at 80°C for 3h to finally obtain a high-nickel lithium metal solid-state battery.
[0063] The high nickel metal lithium solid-state battery of Example 4 was tested by the aforementioned test method. The energy value at constant volume at 100°C was 22.16Wh, and the specific energy was 345.11Wh / kg. Figure 3 .
[0064] Example 5: Preparation of high nickel metal lithium solid-state battery
[0065] The only difference compared with Example 1 is that:
[0066] The prepolymer solution in Example 5 is prepared by the following scheme: ethylene glycol n-butyl ether after dehydration by molecular sieve is used as the ultra-high temperature resistant main solvent, and the lithium salt LiFSI is added thereto and mixed, wherein the lithium salt concentration is 2.6 mol / L, and additives 2wt.% LiODFB, 2wt.% FEC and 1wt.% PES are added and mixed to obtain a basic electrolyte; polyethylene glycol dimethacrylate and triethylene glycol dimethacrylate are added to the basic electrolyte in a molar ratio of 1:1 (the total mass accounts for 4.5% of the basic electrolyte), and then a CMAB initiator is added (accounting for 0.5% of the total mass of the multi-branched copolymer monomer), and after stirring for 8 hours, a prepolymer solution is obtained.
[0067] The prepolymer solution of Example 5 was assembled into a blocked battery, and the EIS test showed that the ionic conductivity at 25°C and 100°C was 2.05×10 -3 S / cm, 7.37×10 -3 S / cm, see attached Figure 1 .
[0068] In the in-situ polymerization of Example 5: under an inert atmosphere, the prepolymer liquid is injected into the high-nickel lithium metal battery dry cell at an injection volume of 1.8g / Ah, and then placed in a vacuum oven for evacuation twice, each time maintaining the pressure for 15 minutes (vacuum degree -0.08MPa) to remove residual air inside the electrode, and then the battery is sealed to obtain a preliminary impregnation battery; the preliminary impregnation battery is impregnated at room temperature and then in-situ polymerized in an oven at 80°C for 3h to finally obtain a high-nickel lithium metal solid-state battery.
[0069] The high nickel metal lithium solid-state battery of Example 5 was tested by the aforementioned test method. The energy value at constant volume at 100°C was 22.14Wh, and the specific energy was 344.8Wh / kg. Figure 3 .
[0070] Comparative Example: Preparation of Metal Lithium Batteries
[0071] The only difference compared with Example 1 is that:
[0072] The prepolymer solution in the comparative example is prepared by the following scheme: ethylene glycol dimethyl ether (existing technology, not resistant to ultra-high temperature) after dehydration by molecular sieve is used as the main solvent, and the lithium salt LiFSI is added thereto and mixed, wherein the lithium salt concentration is 6 mol / L, and an equal volume of co-solvent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether is added to the ultra-high temperature resistant main solvent to obtain a basic electrolyte; polyethylene glycol dimethacrylate and triethylene glycol dimethacrylate are added to the basic electrolyte in a molar ratio of 1:1 (the total mass accounts for 4.5% of the basic electrolyte), and then a CMAB initiator is added (accounting for 0.5% of the total mass of the multi-branched copolymer monomer), and stirred for 8 hours to obtain a prepolymer solution.
[0073] In the comparative example, in situ polymerization: under an inert atmosphere, the prepolymer liquid was injected into the metal lithium battery dry cell at an injection volume of 1.8g / Ah, and then placed in a vacuum oven for evacuation twice, each time maintaining the pressure for 15 minutes (vacuum degree -0.08MPa) to remove residual air inside the electrode, and then the battery was sealed to obtain a preliminary impregnation battery; after the preliminary impregnation battery was impregnated at room temperature, in situ polymerization was carried out in an oven at 80°C for 2h to finally obtain a metal lithium solid-state battery.
[0074] The above test method was used to test the performance of the metal lithium solid-state battery of the comparative example. The energy value at constant volume at 100°C was 26.25Wh, and the specific energy was 408.8Wh / kg. Figure 3 After 100 cycles at 100℃, the capacity retention rate is 80.6%, see Appendix Figure 4 .
[0075] The ultrahigh temperature resistant electrolytes prepared in Examples 1 to 5 and the electrolytes prepared in the comparative example were subjected to DSC tests. The test conditions were: the starting temperature was room temperature, the ending temperature was 180°C, the heating rate was 5°C / min, and the protective atmosphere was nitrogen. The test results are shown in the attached Figure 2 .
[0076] Analysis Attachment Figure 2It can be seen that the ultra-high temperature resistant electrolyte prepared in Example 1 has no peak within the test temperature range, indicating that there is no phase change within 20 to 180°C and the performance is stable; Examples 2 and 3 are consistent with Example 1, so the curve is not repeated in the figure. The ultra-high temperature resistant electrolyte prepared in Example 4 has an exothermic peak in the range of 136 to 145°C, indicating that an exothermic reaction occurs in the electrolyte at this time; the results of Example 5 are similar to those of Example 4, so the curve is not repeated in the figure. The electrolyte prepared in the comparative example has an exothermic peak in the range of 115 to 140°C, indicating that the thermal stability of the electrolyte is lower than that of the electrolytes in other examples.
[0077] according to Figure 2 , 3 By comparing the DSC, energy value and capacity retention rate of 4, it was found that pyrrole ionic liquid solvents are more suitable for high-nickel metal lithium solid-state batteries, and the cycle stability performance of the prepared high-nickel metal lithium solid-state batteries is relatively optimal.
[0078] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the claims attached to the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the claims, or the equivalent forms of such scope and boundaries.
Claims
1. An ultrahigh temperature resistant electrolyte, characterized in that: The electrolyte is obtained by in-situ polymerization using the following raw materials: a basic electrolyte, a multi-branched copolymer monomer and an initiator. The basic electrolyte contains a lithium salt and an ultra-high temperature resistant main solvent. The concentration of the lithium salt in the basic electrolyte is 0.1 to 3 mol / L. The ultra-high temperature resistant main solvent includes an ether solvent and / or a pyrrole ionic liquid.
2. The ultrahigh temperature resistant electrolyte according to claim 1, characterized in that: The ether solvent is any one of ethylene glycol dimethyl ether, ethylene glycol n-butyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dibutyl ether and 18-crown-6.
3. The ultrahigh temperature resistant electrolyte according to claim 1, characterized in that: The pyrrole ionic liquid is any one of 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidine bis(trifluoromethanesulfonyl)imide and N-methyl-N-methoxyethylpyrrolidine bis(trifluoromethanesulfonyl)imide.
4. The ultrahigh temperature resistant electrolyte according to any one of claims 1 to 3, characterized in that: The basic electrolyte contains additives, and the additives account for 3% to 5% of the mass of the basic electrolyte.
5. The ultrahigh temperature resistant electrolyte according to claim 4, characterized in that: The additive is any two or three of lithium difluorooxalatoborate, 1,3-propylene sultone, lithium difluorophosphate, ethyl propionate, fluoroethylene carbonate and vinylene carbonate.
6. The ultrahigh temperature resistant electrolyte according to any one of claims 1 to 5, characterized in that: The lithium salt is any one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide) and lithium difluorooxalatoborate.
7. The ultrahigh temperature resistant electrolyte according to claim 6, characterized in that: The mass ratio of the basic electrolyte to the multi-branched copolymer monomer is (94.0-96.0):(4.0-6.0).
8. The ultrahigh temperature resistant electrolyte according to claim 7, characterized in that: The multi-branched comonomer is any two of polyethylene glycol dimethacrylate, polyethylene glycol methyl ether acrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate and trifluoroethyl methacrylate; the initiator is azobisisobutyronitrile or 1-((cyano-1-methylethyl)azo)formamide.
9. A high nickel metal lithium solid-state battery, characterized in that: It comprises a high-nickel positive electrode and the ultra-high temperature resistant electrolyte according to any one of claims 1 to 8, wherein a ceramic solid electrolyte layer is arranged on the high-nickel positive electrode, and the ceramic solid electrolyte layer is located between the high-nickel positive electrode and the ultra-high temperature resistant electrolyte.
10. The high nickel metal lithium solid-state battery according to claim 9, characterized in that: The ceramic solid electrolyte layer is a nano-scale LATP ceramic electrolyte layer, and its thickness is 450nm-500nm.
Citation Information
Patent Citations
High-temperature-resistant electrolyte, secondary battery and application thereof
CN115425292A
High-temperature-resistant flame-retardant electrolyte and preparation method and application thereof
CN118173881A
Polyacrylate solid polymer electrolyte and preparation method thereof and application thereof in solid lithium battery
CN108183258A
Double-layer solid electrolyte film for lithium battery and preparation method thereof
CN112599847A
Wide-temperature-range solid electrolyte, solid-state lithium battery and preparation method of solid-state lithium battery
CN115588777A